Corporate Social Responsibility in Vietnamese Companies: An Exploration of Practices, Motivations and Barriers - Hung, Ta Huy; Nguyen, Phuong Mai; Luu, Thi-Minh-Ngoc; Nguyen, Anh Tuan (International Review of Management and Marketing, 2025)
It is evitable that companies worldwide are under greater pressures to take their corporate social responsibility due to the evolving consumer expectations, regulatory changes, and the recognition of its potential impact on financial performance. Vietnamese companies are not an exception. However, there are limited studies in Vietnam focusing on the factors affecting how CSR initiatives are implemented in large companies. In such a context, this paper explores the practices, motivations and barriers to CSR implementation in Vietnamese companies. We selected 20 large companies from the list of 500 Vietnamese largest companies (VNR500) and approached the managers to conduct in-depth interviews. From the results of interviews with managers, we analyzed, classified and synthesized factors that encourage or hinder CSR practices of these companies through the lens of managerial practitioners. Our findings show that external forces are critical in motivating large Vietnamese companies to take CSR initiatives in order to build good public image and firm reputation. Furthermore, some obstacles to CSR in the Vietnamese context were also identified among which “lack of time”, “lack of employee participation” and “loose connection with the company’s core business” are three most prominent ones. Consequently, we recommend Vietnamese companies to take a series of actions to engage employees and turn CSR activities into “common things” that have been integrated into their daily business operations.